Perlindungan Hukum Bagi Konsumen Dalam Investasi Online Reksadana - Larisha Amalia Pratiwi; Abdul Qahar; Andi Risma (Qawanin Jurnal Ilmu Hukum, 2020)
This study intends to identify and explain the legal regulations related to online mutual fund investment in Indonesia and the legal protection aspects of investors as consumers in online mutual fund investment. The research was conducted using the normative method by examining secondary data and supported by interview data. The results showed that in the context of online mutual fund investment in Indonesia it is not specifically regulated, but related to the legal arrangement it is regulated in several laws and regulations. Meanwhile, the aspect of legal protection for online mutual fund investment consumers in Indonesia can refer to several laws and regulations, namely. Based on the Capital Market Law, initially, the capital market was under the supervision of Bapepam-Lk, but in 2011 the Government & DPR agreed to establish OJK to replaces Bapepam-Lk. Based on the Financial Services Authority Law, the form of legal protection for the OJK for consumers is preventive and repressive. Meanwhile, based on the Consumer Protection Law, a form of legal protection for investors, namely in 2001 the Government established the National Consumer Protection Agency (BPKN) which then formed the Consumer Dispute Resolution Agency (BPSK) at the regional level. Abstrak Penelitian ini bermaksud untuk mengetahui dan menjelaskan mengenai pangaturan hukum terkait investasi online reksadana di Indonesia dan aspek perlindungan hukum terhadap investor selaku konsumen dalam investasi online reksadana. Penelitian dilakukan dengan metode normative dengan mengkaji data sekunder dan didukung oleh data wawancara. Hasil penelitian menunjukkan bahwa dalam konteksnya investasi online reksadana di Indonesia tidak diatur secara spesifik, namun terkait pengaturan hukum nya diatur dalam beberapa peraturan perundang-undangan. Sedangkan, aspek perlindungan hukum terhadap konsumen investasi reksadana online di Indonesia dapat merujuk pada beberapa peraturan perundang-undangan yakni : Berdasarkan Undang-Undang Pasar Modal awalnya pasar modal dibawah pengawasan Bapepam-Lk, namun pada tahun 2011 Pemerintah dan DPR sepakat mendirikan OJK untuk menggantikan Bapepam-Lk. Berdasarkan Undang-Undang Otoritas Jasa Keuangan, bentuk perlindungan hukum OJK terhadap konsumen yakni secara preventif dan represif. Sedangkan, berdasarkan Undang-Undang Perlindungan Konsumen, bentuk perlindungan hukum terhadap investor yakni pada tahun 2001 Pemerintah membentuk Badan Perlindungan Konsumen Nasional (BPKN) yang kemudian membentuk Badan Penyelesaian Sengketa Konsumen (BPSK) di tingkat daerah.